FAKTOR - FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI PEKANBARU DAN PADANG - Yogi Andrian; Emrinaldi Nur DP; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to examine the effect of responsiveness, ethics auditor, bussiness scale, and resources availability on audit quality and to examine the effect of work experience as a moderating the effect of responsiveness, ethics auditor, bussiness scale and resources availability on audit quality. The population in this study were all Public Accounting Firm were registered in IAPI (Institute of Public Accountants Indonesia) in Pekanbaru and Padang, which amounts to 16 (Sixteen) Public Accounting Firm. Samples determined using purposive sampling method. Methods of data collection in this study using questionnaires. While the method of data analysis and hypothesis testing using Structural Equation Model-Partial Least Square (PLS-SEM). The results showed that the responsiveness, ethics auditor, bussiness scale, and resources availability significantly affect the audit quality. Responsiveness and ethics auditor are moderated by work experience significantly affect the audit quality. While the bussiness scale and resources availability are moderated by work experience do not significantly affect the audit quality. R2 value equal to 0.954, which means 95.4% of the independent variables in this study could affect the dependent variable, while the remaining 4.6% is explained by other variables that are not included in this study.Keywords: Quality audit, work experience, responsiveness, business scale, resources availability